Electrical characteristics of point to plate corona systems with a biased cylinder - Campos, J. Sinezio C. [UNESP]; Giacometti, Jose A.; Oliveira, Osvaldo N. (My University, 1992)
In this paper we report on current-voltage characteristics and radial current distributions of a corona system in which the point is placed at the axis of a biased metallic cylinder. When a grid is inserted between the point and the plate, in the so-called corona triode, the plate current decreases drastically but the current distribution uniformity over the plate is improved. Also discussed is the importance of the uniformity in the current distribution for the charging process of dielectric foils. In this regard the corona triode behaves much in the same way as the scorotron systems usually employed in electrophotography.